Design of decision support system for business feasibility study using SMART method. Issue 3 (March 2021) - Septiana, Y; Sofiah, E; Mulyani, A; Setiawan, R
Abstract: The business feasibility study is critical to be used as the main foundation to avoid and prevent the occurrence of unwanted risks related to losses in businesses run by business people in the services, trade, and manufacturing sectors. Through a business feasibility study, business actors will get an initial description of the feasibility or inadequacy of a business plan to be implemented, so that businesses get a prediction of decisions about the business to be carried out. Utilization of information technology in terms of business feasibility study decision support systems will help businesses to improve quality, productivity, efficiency, effectiveness, minimize risk, and solve business-related problems that will be run. This research aims to design a business feasibility study decision support system to assess the feasibility of implementing business in services, trade, and manufacturing. Decision-making method in a decision support system designed using Simple Multi Attribute Rating Technique (SMART), where the decision making criteria is based on economic feasibility studies with several predetermined attributes, namely Break Even Points (BEP), Net Present Value (NPV), Internal Rate of Return (IRR), Average Rate of Return (ARR), Benefit/Cost Ratio (B/C Ratio) and Payback Period (PP) and Profitability Index (PI). The results of this research are in the form of a business feasibility study decision support system that can be used to assess the extent of the benefits that can be obtained in carrying out business activity and is a material for consideration in making a decision, whether to accept or reject a planned business idea measured by benefits to be received, both financial and social benefits.